2021
DOI: 10.1108/ijlm-04-2021-0230
|View full text |Cite
|
Sign up to set email alerts
|

Do organizational subcultures matter? A case study of logistics and supply chain management

Abstract: PurposeThis interdisciplinary investigation examines the topics of organizational climate and subcultures, which have received scant attention in the supply chain literature, highlighting the potential importance of these social dynamics to supply chain management phenomena.Design/methodology/approachThe authors use a single-organization revelatory case study design, qualitatively analyzing coded interviews and observations of participants.FindingsThe authors’ findings indicate that a firm's organizational cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(89 reference statements)
0
5
0
1
Order By: Relevance
“…subculture actor as a case study. Previous case study pertaining subculture shows that certain marginalized subculture has its own aesthetic, it can be seen from this one case study on one ethnic Chinese subculture that they underwent a great struggle to be recognized for their Cap Gomeh and Chinese new year celebration (Alkadrie et al, 2017;Mello & Schloemer, 2022). From this case study, it can be concluded that as long as there is movement within a certain subculture, integration into other social arenas will be formed.…”
Section: Unnes Journalsmentioning
confidence: 72%
See 2 more Smart Citations
“…subculture actor as a case study. Previous case study pertaining subculture shows that certain marginalized subculture has its own aesthetic, it can be seen from this one case study on one ethnic Chinese subculture that they underwent a great struggle to be recognized for their Cap Gomeh and Chinese new year celebration (Alkadrie et al, 2017;Mello & Schloemer, 2022). From this case study, it can be concluded that as long as there is movement within a certain subculture, integration into other social arenas will be formed.…”
Section: Unnes Journalsmentioning
confidence: 72%
“…In addition to that, the subcultural approach can be a reference to similar other studies which focused in the same topic. The study of subcultures has always been related to the ideology of resistance and and pertaining class struggle, one study on Deadheads subculture focused on the dialectic identity of the subculture that has been developed (Smith, 2022;Smith, S., 2022), another study shows how the identity and value of subculture in their working environment (Mello & Schloemer, 2022).…”
Section: Unnes Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tem-se então que os membros destas subculturas podem exibir comportamentos baseados nos valores e normas das suas antigas organizações ao invés de assumirem a nova entidade. [Mello e Schloemer, 2022].…”
Section: Discussionunclassified
“…This happens particularly in project teams where team members might develop their way to manage organizational interactions according to the methodology, targets, and contingencies [54]. These values are usually consistent with their sense of priority, which is why subculture members can act differently [56]. In these contexts, the CVF still proves suitable for application at a specific organizational unit or team level, helping to display the combination of cultural values that can partly differ from the overall organizational culture and evaluate possible misalignments with the desired scenario at the company level.…”
Section: Bmentioning
confidence: 99%